2020
DOI: 10.1007/s42452-020-2209-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationship design of knowledge co-creating cluster: traditional Japanese architectural industry

Abstract: Increased global mobility led by remarkable developments and the extension of public infrastructure has brought about not only the possibility of further conventional static relationship design, but also the importance of dynamic relationship design as well. Operating on the assumption that this catalytic environmental change will occur in the form of increased mobility, every type of organization-regardless of industrial sector, size, or profit status-is faced with the need to design and manage this connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For example, in a co-design situation, each individual designer will at each moment influence the designers' own and other designers' experiences, which they will then enter in interaction through collaboration with each other as the interactive level rises, pushed forward by the motivation that was created by the sharing of experiences (Matsumae et al 2020). This will, in return, create the possibility of shared results out of the interactive moment by pushing for the emergence of new interactional context, such as shared understanding, shared knowledge and shared perceptions.…”
Section: Influence On Interactions In Co-designmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a co-design situation, each individual designer will at each moment influence the designers' own and other designers' experiences, which they will then enter in interaction through collaboration with each other as the interactive level rises, pushed forward by the motivation that was created by the sharing of experiences (Matsumae et al 2020). This will, in return, create the possibility of shared results out of the interactive moment by pushing for the emergence of new interactional context, such as shared understanding, shared knowledge and shared perceptions.…”
Section: Influence On Interactions In Co-designmentioning
confidence: 99%
“…There is a need to focus on what causes interactions to reach high interactive levels. By defining design in the words of Taura & Nagai (2011) as “the process of composing a desired figure toward the future,” we can see how social design needs to focus on human interaction mechanisms to attain a well-being society (Matsumae, Matsumae & Nagai 2020). From that point, to challenge new social possibilities, there appears to be a need for better experiences in social interactions, even in design, that can help sustain co-design as a desirable future.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, co-creative collaboration is defined as a collaboration in which individuals share tacit knowledge and create something together, while cooperative collaboration is explained as a collaboration in which individuals do not share tacit knowledge and act together to achieve a given goal. (Matsumae et al, 2020;Matsumae and Nagai, 2018). Therefore, co-creative collaboration was determined when both (1) the sharing of tacit knowledge and (2) the formation of tacit knowledge was observed, which distinguished it from cooperative collaboration.…”
Section: Evaluation Of Collaborationmentioning
confidence: 99%
“…The formation of concepts demands creative thinking (Casakin, 2007), and thinking patterns in which explicit and 'inexplicit' concepts are continuously intertwined lead to creative design ideas (Taura et al, 2012). Experiments have revealed that the co-creative process, which by definition includes transferring tacit knowledge to tacit knowledge, increases shared contexts and engagement (Matsumae and Nagai, 2020). In this study, the authors applied both co-creative and non-co-creative processes to a learning experiment and compared their results.…”
Section: Introductionmentioning
confidence: 99%